Epidemiological Studies to Support the Development of Next Generation Influenza Vaccines - Joshua G. Petrie; Aubree Gordon (Vaccines, 2018)
The National Institute of Allergy and Infectious Diseases recently published a strategic plan for the development of a universal influenza vaccine. This plan focuses on improving understanding of influenza infection, the development of influenza immunity, and rational design of new vaccines. Epidemiological studies such as prospective, longitudinal cohort studies are essential to the completion of these objectives. In this review, we discuss the contributions of epidemiological studies to our current knowledge of vaccines and correlates of immunity, and how they can contribute to the development and evaluation of the next generation of influenza vaccines. These studies have been critical in monitoring the effectiveness of current influenza vaccines, identifying issues such as low vaccine effectiveness, reduced effectiveness among those who receive repeated vaccination, and issues related to egg adaptation during the manufacturing process. Epidemiological studies have also identified population-level correlates of protection that can inform the design and development of next generation influenza vaccines. Going forward, there is an enduring need for epidemiological studies to continue advancing knowledge of correlates of protection and the development of immunity, to evaluate and monitor the effectiveness of next generation influenza vaccines, and to inform recommendations for their use.